Total sleep deprivation selectively impairs motor preparation sub-stages in visual search task: Evidence from lateralized readiness potentials - Song, Tao; Du, Fangchong; Xu, Lin; Peng, Ziyi; Wang, Letong; Dai, Cimin; Xu, Mengmeng; Zhang, Ying; Shao, Yongcong; Weng, Xiechuan; Li, Shijun (Frontiers in Neuroscience, 2023)
Many studies have provided evidence of a damage effect triggered by total sleep deprivation (TSD). However, it remains unclear whether the motor preparation processing is affected by TSD. In the current study, 23 volunteers performed a stimulus-response compatibility visual search task before and after TSD while undergoing spontaneous electroencephalography. Repeated-measures analysis of variance revealed that: Compared with that at baseline, the visual search task’s accuracy decreased after TSD, while the response time variance increased significantly. The peak amplitude of the stimulus-locked lateralized readiness potential induced by a compatible stimulus was significantly more negative than that induced by an incompatible stimulus before TSD, whereas this difference was not significant after TSD. However, when taking sleep status into consideration, there were no significant main or interaction effects on response-locked lateralized readiness potentials. Our findings suggest that TSD damages visual search behavior, selectively impairs the earlier sub-stages of motor preparation (sensory integration). These findings will provide a new perspective for understanding the effects of sleep loss.